Object modeling by geometric matching for a prospective portable 3D scanner - Hügli, Heinz; Jost, Timothée (My University, 1999)
With the evolution of 3D-scanner technology, the combined measurement of color and geometry of objects and scenes becomes feasible within a portable device. It opens new perspectives for the generation of virtual 3D models and applies to domains like multimedia, museography, reverse engineering... Several scanner technologies and object modeling schemes are possible. This paper discusses some of these possibilities and shows why the modeling by geometric matching of object views efficiently assists a universal portable device in the modeling task. It introduces the concept of a global architecture involving a remote portable 3D scanner linked to a powerful modeling facility and presents examples for the expected results.
Keywords: 3D scanner; object modeling; multimedia; virtual worlds; portable scanner